A weighting procedure to analyse the Indoor Environmental Quality of a Zero-Energy Building. (October 2020) - Danza, Ludovico; Barozzi, Benedetta; Bellazzi, Alice; Belussi, Lorenzo; Devitofrancesco, Anna; Ghellere, Matteo; Salamone, Francesco; Scamoni, Fabio; Scrosati, Chiara
Abstract: The Indoor Environmental Quality (IEQ) is a basic requirement for the design of energy-efficient buildings since it affects the occupants' well-being and health inside buildings. Over the years, the issue of IEQ has been widely investigated under different perspectives: from the first experiments aimed at assessing the physiological response of individuals it has become a human-centric concept. In recent years, new paradigms have influenced buildings design towards sustainable and highly efficient constructions. Zero-Energy Buildings (ZEBs) are the current challenge which should be appropriately addressed with a holistic approach to achieve excellent IEQ and energy efficiency levels. Thermal, visual and acoustic comfort and indoor air quality are the most important Indoor Environmental Factors (IEF) characterizing the overall environmental condition of indoor spaces. However, there is no standard method to calculate the overall IEQ level of a building by monitoring and aggregating all individual aspects of comfort. This article aims to bridge this gap, proposing a method to define weighting factors of IEFs. A survey was carried on 100 participants out in a fully monitored Zero-Energy full-scale test building to collect and analyse the answers of the sample about their evaluation of IEFs. The collected data of questionnaire-based IEQ responses were treated with a multiple linear regression model. The results prove that IEQ is affected mostly by IAQ during the test. The proposed weighting factors were applied to rank the monitoring-based IEFs. The comparison between objective (monitoring-based) and subjective (questionnaire-based) analyses shows how the former underestimates IEQ with respect to the latter. Highlights: A questionnaire-based survey on IEQ is carried out involving 100 participants. Weighting factors are proposed to classify the indoor comfort of ZEB. An IEQ design-based index calculated through an aggregation of IEF is proposed. The objective and subjective comparison suggests that the former underestimates IEQ. The consistency of the proposed design quantities and their limit values are discussed.